instalação performática imersiva: estar experimentos I e II - paranhos, stephanie piva (2015)
This study aims to promote a line of analysis and reflection for understanding the presence and the public's relationship with the performative act in the sense that it involved not just as an observer but as a participant of the work, by performing two “performative-immersive experiences” in the cities of Ribeirão Preto and Uberlândia, Minas Gerais, respectively. The main theoretical and artistic influences of the study are: Nathalie Goldberg (2008), which proposes daily exercise spanning the experience and the experience of “being”, based on automatic writing, which has become a very important process for development research; Marina Abramovic (2012), which, by proposing exercises that explore the physical and mental limits of the performer and the public, contributing to the creation of the procedures of experience and preparation before the performance, which involves a way of life that seeks to find itself, being the language of performance art and the channel for exchanges and demonstrations of their questions, spells, feelings and ideas; Lygia Clark (1984), which, by encompassing throughout his career proposals and theories on the relationship artist and audience, influenced the creation of an experience that dilute the separation between the applicant and spectator; Punchdrunk and Rimini Protokoll, which, with the proposed immersive and audiotour theater, are contemporary references that contribute to the reflection on the participant within the current scene. Therefore, the research focuses on the world of physical experience to create immersive performance installations, in order to observe the participant's presence relationships, synesthetic perception and intimate relationship between energy flow proponent and participant, the latter being placed in atypical situations related to time, space and sensitive perception